Abstraction as Material Translation : An Artistic Reflection of (Re)Presentation - Knuuttila, Tarja; Johansson, Hanna; Carrillo, Natalia (Routledge, 2024)
In this chapter we put the work of Finnish conceptual and environmental artist, Lauri Anttila (1938–2022), in dialogue with discussions of the practices of scientific and mathematical representation. We are interested in the counterintuitive claim that abstraction crucially involves concreteness: instead of thinking about abstraction in opposition to the concrete, we focus on the importance of concrete actions, methods, and instruments in achieving abstract representations. In particular, we study the process of abstraction as a chain of “material translations” that engages with our cognitive abilities, representational and other artefacts, and diverse epistemic contexts in various ways. To examine and illustrate abstraction as material translation, we study Anttila’s work, Homage to Werner Holmberg (1985–1986), which parodies scientific representation in seeking to render with scientific methods the landscapes in the paintings of Werner Holmberg, a Finnish landscape artist from the 19th century. We study the striking parallels between Anttila’s artwork and the writings on scientific representation by Bruno Latour and Michael Lynch. The comparison of these analyses of scientific abstraction, rendered both artistically and through scholarly discussion, allows us to widen the scope of the philosophical discussion of abstraction in science that has so far been too narrowly focused on omission.
Keywords: tieteenfilosofia; taide; abstrakti taide; representaatio; taideteokset; semiotiikka; oppihistoria